An Investigation of English Department Students’ Speaking Difficulties on Online Learning During Covid-19 Pandemic - Welly Ernando Sihombing; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
This study aimed to investigate the difficulties of 2019 English Department students of UNP (Universitas Negeri Padang) that learn English speaking through online learning during COVID-19 pandemic. The researcher chose English department students’ year 2019 as the sample and the total is 45 students. In collecting the data, the researcher used questionnaire and speaking test. Results of analysis showed that vocabulary (93.3%) and fluency (93.3%) were the predominant problem that causes their difficulty in speaking English. The problem of technology (91.75%) such as no strong and stable signal, insufficient facilities, limited knowledge on using the application and limited money to buy the internet quota also seriously worsened their performance in speaking English and increased their low participation (73.3%). The findings suggest pedagogical implications for promoting the students’ speaking English and provide the good internet facilities and other networking support systems if online learning will be applied in the future.